2013
DOI: 10.1111/php.12179
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of Glycosylated Derivatives of a Chlorin, Isobacteriochlorin and Bacteriochlorin for Photodynamic Theragnostics: Discovery of a Two‐photon‐absorbing Photosensitizer

Abstract: The photophysical properties of a chlorin, isobacteriochlorin, and bacteriochlorin built on a core tetrapentafluorophenylporphyrin (TPPF20) and the non-hydrolysable para thioglycosylated conjugates of these chromophores are presented. The photophysical characterization of these compounds was done in three different solvents to correlate to different environments in cells and tissues. Compared to TPPF20 these conjugates have greater absorption in the red region of the visible spectrum and greater fluorescence q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 81 publications
1
28
0
Order By: Relevance
“…Here two separate near-infrared photons have to arrive at the PS molecule virtually simultaneously, and if they are absorbed at the same time they will be equivalent to a single photon of half the wavelength [130]. However, the need for simultaneous absorption of both photons means that an extremely high peak power density (in the order of GW/cm 2 ) is required.…”
Section: Future Directionsmentioning
confidence: 99%
“…Here two separate near-infrared photons have to arrive at the PS molecule virtually simultaneously, and if they are absorbed at the same time they will be equivalent to a single photon of half the wavelength [130]. However, the need for simultaneous absorption of both photons means that an extremely high peak power density (in the order of GW/cm 2 ) is required.…”
Section: Future Directionsmentioning
confidence: 99%
“…These com-pounds were also studied for two photon fluorescence imaging on Chinese hamster ovary cells and we found that IGlc 4 has good two photon absorption (TPA) between 760 and 880 nm, and the cross section is 24.5 GM at 860 nm. 93 …”
Section: Substituted Fluorinated Porphyrinoids For Biological Applicamentioning
confidence: 99%
“…Light with λ >850 nm, however, does not provide enough energy for excitation of 3 O 2 to 1 O 2 [100,106]. This drawback is eliminated by simultaneous absorption of two photons by the PS, to provide the same energy as a single photon of shorter wavelength [107]. …”
Section: Photosensitizersmentioning
confidence: 99%